Issues and Challenges in Cultural Heritage Tourism in Nepal - Baral, Aakriti (Nepalese Journal of Business, 2024)
This study examined the issues and challenges in cultural heritage tourism in Nepal. Sustainability of cultural heritage tourism is the dependent variable. The selected independent variables are government policy and regulations, community participation and empowerment, tourist behaviour and preferences, climate change and environmental concerns, technological advancement and innovations and economic factor and market demand. The primary source of data is used to assess the opinions of respondents regarding government policy and regulations, community participation and empowerment, tourist behaviour and preferences, climate change and environmental concerns, technological advancement and innovations and economic factor and market demand for sustainability of cultural heritage tourism. The study is based on primary data of 121 respondents. To achieve the purpose of the study, structured questionnaire is prepared. The correlation and multiple regression models are estimated to test the significance and importance of issues and challenges in cultural heritage tourism in Nepal. The study showed a positive impact of government policy and regulations on sustainability of cultural heritage tourism. It indicates that strong government policy and regulations leads to increase in sustainability of cultural heritage tourism. Similarly, the study showed a positive impact of community participation and empowerment on sustainability of cultural heritage tourism. This implies that increased community participation and empowerment leads to the increase in sustainability of cultural heritage tourism. Likewise, the study revealed a positive impact of tourist behaviour and preferences on sustainability of cultural heritage tourism. It indicates that positive tourist behaviour and preferences leads to increase in sustainability of cultural heritage tourism. In addition, the study observed a positive impact of technological advancement and innovations on sustainability of cultural heritage tourism. It indicates that the technological advancement and innovations leads to increase sustainability of cultural heritage tourism. Further, the study observed a positive impact of climate change and environmental concerns on sustainability of cultural heritage tourism. It implies that higher level of positive change in climate change and environmental concerns, drives sustainability of cultural heritage tourism. Moreover, the study observed a positive impact of economic factor and market demand on sustainability of cultural heritage tourism. It indicates that the higher economic factor and market demand stimulates sustainability of cultural heritage tourism.